Effect of Sucrose Esters and Sunflower Oil Addition on Crystalline Microstructure of a High-melting Milk Fat Fraction - Martini, Silvana (2002)
The effects of sunflower oil (SFO) and the sucrose esters (SE) P-1670, P-170, and S-170 on crystalline microstructure of a high-melting milk fat fraction (HMF) was studied by polarized-light microscopy (PLM) and confocal laser scanning microsopy (CLSM). The addition of SFO markedly diminished crystal size and delayed crystallization kinetics, as observed in PLM images. Addition of P-1670 modified crystallization behavior only slightly. Addition of P-170 and S-170, however, markedly diminished crystal size and led to more transparent crystals, with lower amount of solids in each crystal. These results show that the microstructural properties of HMF were modifed by addition of SFO and by addition of SPE with low HLB.